144k views
5 votes
PLEASE SOMEONE HELP I TRULY DO NOT UNDERSTAND

Find F^-1(x), the inverse of F(x).

f(x)-9x^3-4
Show your work please because I don’t understand.

PLEASE SOMEONE HELP I TRULY DO NOT UNDERSTAND Find F^-1(x), the inverse of F(x). f-example-1

1 Answer

0 votes

Hi there!


\large\boxed{f^(-1)(x) = \sqrt[3]{(x+4)/(9) } }


f(x) = 9x^(3) - 4

Find the inverse by replacing f(x) with y and swapping the x and y variables:


x = 9y^(3) - 4

Isolate y by adding 4 to both sides:


x + 4 = 9y^(3)

Divide both sides by 9:


(x+4)/(9)= y^(3)

Take the cube root of both sides:


y = \sqrt[3]{(x+4)/(9) }\\\\f^(-1)(x) = \sqrt[3]{(x+4)/(9) }

User Vishnus
by
5.8k points